SOCIALIZATION OF COCONUT SHELL LIQUID SMOKE AS A DEODORANT OF FOUR-LEGGED LIVESTOCK MANURE IN LOBANG, KARANGANYAR - Nindi Dewi Istiqomah; Ibnu Raju Humam; Esti Mustafida; Nurroh Maya; Dwi Wahyu Priyodigdo (UIN Sunan Kalijaga, 2024)
This study aims to address the issue of unpleasant odors from cattle manure in Dusun Lobang, Karanganyar, Central Java, by applying liquid smoke derived from coconut shells. The primary problem identified is the ammonia odor that disrupts community comfort. The methods employed include observation, socialization, and practical training in liquid smoke production, followed by direct application to livestock shelters. The results indicate that liquid smoke effectively reduces unpleasant odors gradually, with 80% of residents demonstrating understanding and enthusiasm towards the technique. The benefits of this research include improved environmental quality and enhanced knowledge among farmers about waste management. The study's limitations include the gradual reduction of odor and the simplicity of the smoke production technology. Recommendations for future research include long-term studies and the development of more efficient production tools, as well as policy support for implementing similar technologies in other regions. ============================================= Penelitian ini bertujuan untuk mengatasi masalah bau tidak sedap yang dihasilkan dari kotoran ternak sapi di Dusun Lobang, Karanganyar, Jawa Tengah, melalui pengaplikasian asap cair dari tempurung kelapa. Masalah utama yang diidentifikasi adalah bau amonia yang mengganggu kenyamanan masyarakat. Metode yang digunakan meliputi observasi, sosialisasi, dan praktik pembuatan asap cair, serta penyemprotan langsung ke kandang ternak. Hasil penelitian menunjukkan bahwa asap cair efektif mengurangi bau tidak sedap secara bertahap, dengan tingkat pemahaman dan antusiasme warga mencapai 80%. Manfaat dari penelitian ini mencakup peningkatan kualitas lingkungan dan pengetahuan peternak tentang pengelolaan limbah. Keterbatasan penelitian meliputi variabilitas bau yang memerlukan waktu untuk menghilang dan teknologi alat pengolah yang masih sederhana. Rekomendasi untuk penelitian selanjutnya adalah kajian jangka panjang dan pengembangan alat yang lebih efisien, serta dukungan kebijakan untuk penerapan teknologi serupa di daerah lain.